Hydrologically-driven crustal stresses and seismicity in the New Madrid Seismic Zone - Craig, Timothy J.; Chanard, Kristel; Calais, Eric (Nature communications, 2017)
The degree to which short-term non-tectonic processes, either natural and anthropogenic, influence the occurrence of earthquakes in active tectonic settings or ‘stable’ plate interiors, remains a subject of debate. Recent work in plate-boundary regions demonstrates the capacity for long-wavelength changes in continental water storage to produce observable surface deformation, induce crustal stresses and modulate seismicity rates. Here we show that a significant variation in the rate of microearthquakes in the intraplate New Madrid Seismic Zone at annual and multi-annual timescales coincides with hydrological loading in the upper Mississippi embayment. We demonstrate that this loading, which results in geodetically observed surface deformation, induces stresses within the lithosphere that, although of small amplitude, modulate the ongoing seismicity of the New Madrid region. Correspondence between surface deformation, hydrological loading and seismicity rates at both annual and multi-annual timescales indicates that seismicity variations are the direct result of elastic stresses induced by the water load. Large-scale changes in continental water storage have been shown to have an impact on seismicity. Here, the authors show that variation in the rate of microearthquakes in the New Madrid Seismic Zone coincides with hydrological loading in the Mississippi embayment at both annual and multi-annual timescales.